THE CONVERSATION STYLES BETWEEN MAN AND WOMAN IN "AMERICAN TRAITOR: THE TRIAL OF AXIS SALLY" MOVIE - Hutapea, Berliana (Jurnal Review Pendidikan dan Pengajaran, 2024)
This research aims to analyze the conversational style between men and women in the film American Traitor: The Trial of Axis Sally. This research uses qualitative methods to understand the use and impact of derivational affixes in film contexts. Data was collected through observation, transcription and analysis of dialogue and non-verbal cues in the film "American Traitor: The Trial of Axis Sally". Data collection involved acquiring films, transcribing relevant dialogue, noting non-verbal cues, and consulting secondary sources such as reviews and academic articles. Observations were carried out directly in the field, identifying and selecting certain scenes where male and female interactions were very important in the storyline. Data analysis techniques include developing a coding framework, identifying patterns and themes, conducting comparative and contextual analysis, and interpreting findings to understand gender dynamics, interpersonal relationships, and social norms in films. Ethical considerations ensure proper citation and respect for copyright laws. The results of this research indicate that there are significant differences in conversational styles between male and female speakers in the film "American Traitor: The Trial of Axis Sally." Female speakers tend to use lexical hedging, marking questions, and amplifiers, which reflect politeness, hesitation, and emotional expression. In contrast, male speakers more frequently used commands and directions, minimal responses, and thematic content focused on topics such as sports and work, indicating assertiveness and task orientation.